Avoidable 30-day readmissions in patients undergoing vascular surgery. Issue 6 (2nd August 2019) - Knighton, A; Martin, G; Sounderajah, V; Warren, L; Markiewicz, O; Riga, C; Bicknell, C
Abstract: Background: Vascular surgery has one of the highest unplanned 30-day readmission rates of all surgical specialties. The degree to which these may be avoidable and the optimal strategies to reduce their occurrence are unknown. The aim of this study was to identify and classify avoidable 30-day readmissions in patients undergoing vascular surgery in order to plan targeted interventions to reduce their occurrence, improve outcomes and reduce cost. Methods: A retrospective analysis of discharges over a 12-month period from a single tertiary vascular unit was performed. A multidisciplinary panel conducted a manual case-note review to identify and classify those 30-day unplanned emergency readmissions deemed avoidable. Results: An unplanned 30-day readmission occurred in 72 of 885 admissions (8·1 per cent). These unplanned readmissions were deemed avoidable in 36 (50 per cent) of these 72 patients, and were most frequently due to unresolved medical issues (19 of 36, 53 per cent) and inappropriate admission with the potential for outpatient management (7 of 36, 19 per cent). A smaller number were due to inadequate social care provision (4 of 36, 11 per cent) and the occurrence of other avoidable adverse events (4 of 36, 11 per cent). Conclusion: Half of all 30-day readmissions following vascular surgery are potentially avoidable. Multidisciplinary coordination of inpatient care and the transition from hospital to community care after discharge need to be improved. Graphical Abstract: Fifty per cent of all unplanned 30-day readmissions in patients undergoing vascular surgery are potentially avoidable. To reduce this burden, there is a need to take a multidisciplinary approach to optimizing medical care, support the transition from hospital to community care effectively, and develop targeted strategies to patients deemed to be at high risk. Many readmissions avoidable